The Effect of Budgetary Participation on Managerial Performance With Organizational Commitment as A Moderating Variable - Fernando Sihombing, Paquito (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the effect of budgetary participation on managerial performance and examine the role of organizational commitment as a moderating variable. The phenomenon of budgetary participation is a crucial issue in organizations because it can improve transparency, accountability, and the effectiveness of decision-making. This study used a quantitative approach with a survey method of 120 respondents who were middle-level managers in a manufacturing company. Data were analyzed using Moderated Regression Analysis (MRA). The results showed that budgetary participation has a positive and significant effect on managerial performance. In addition, organizational commitment has been shown to strengthen the relationship between budgetary participation and managerial performance. These findings demonstrate the importance of organizational support and managerial involvement in the budgeting process to improve performance quality. This study contributes to the literature on financial management and organizational behavior and provides practical recommendations for companies to improve the effectiveness of their budgeting systems.